PELAKSANAAN PEMBERDAYAAN EKONOMI PROGRAM ZMART DALAM MENINGKATKAN KESEJAHTERAAN UMK (USAHA MIKRO KECIL) DI BAZNAS PROVINSI BALI - Budiman, Aris; Kusjuniati, Kusjuniati; Agrosamdhyo, Raden (widya balina, 2025)
Many people in the Provincial City have established micro businesses, both small and medium businesses. The types of businesses that are widely run by people in the Provincial City are micro businesses in the form of shops or grocery stalls. Realizing the enormous potential of MSMEs (Micro and Small Enterprises) for the economic development of the community, the Bali Provincial Baznas has launched a program that can help people in the Bali Province to further optimize the businesses they run, namely the Zmart (Zakat Market) program. The purpose of this discussion is to determine the implementation and results of the economic empowerment of the Zmart Program programmed by the Bali Provincial BAZNAS to improve the welfare of MSMEs (Micro and Small Enterprises) in the city of Denpasar, Bali. This research method is qualitative research, data collection is carried out using Observation, Interview and Documentation techniques. Data analysis is carried out using qualitative descriptive analysis. Triangulation method. The results of this study include the implementation of the economic empowerment of the Zmart program which has been implemented in August 2023 well and is running in accordance with the objectives of the Zmart program. And improving the welfare of UMK (Micro and Small Enterprises), especially in Denpasar City, Bali Province, which has benefited from the implementation of the Zmart BAZNAS Bali Province program, both in terms of economy and social.